The maintenance of Malangan Javanese dialect in the trade transactions in the border area of Malang and Blitar - Ismatul Khasanah; Roosi Rusmawati; Khilmi Mauliddian (LITERA, 2023)
This study aims to observe the form of Javanese language in Malangan dialect in the trade transactions occurring in the border area between Malang and Blitar.  The research design used in this study is of qualitative research, namely providing an overview of a certain phenomenon as clear as possible.  The purpose of this research is to become a reference to a policy design in maintaining Malangan dialect, especially in border communities. The results of this research show that the maintenance of Javanese language in Malangan dialect in the domain of trade transaction in border areas is still well maintained. The process can be acknowledged from the words chosen and spoken in the domain of trade transactions by both buyers and sellers which represent the characteristics of Malangan dialect. In addition, even though there are sellers and buyers from different regions speaking different dialects, it does not restrain the native speakers of Malangan dialect from understanding their utterances. The factors that strengthen the maintenance of the Javanese language in Malangan dialect in the domain of trade transaction in the Malang and Blitar border area are: custom, speaker’s identity, geographical area, and a sense of dissimilarity from having and using different dialect.Keywords: border area, language maintenance, Malangan dialect, Mataraman dialect, trade transactions